Penetapan Anak dari Perkawinan Campuran Ditinjau dari Undang-Undang Perkawinan - Widasari, Widasari; Dewi, Sartika; Abas, Muhamad (LPPM Universitas Ekasakti Padang, 2024)
Law Number 1 of 1974, amended by Law Number 16 of 2019 concerning Marriage, regulates mixed marriages in Article 57, affirming that marriage between two individuals in Indonesia subject to different laws due to differences in nationality and one party being an Indonesian citizen. This research aims to analyze the legal consequences of mixed marriages on the establishment of children according to this Law. The study employs a normative juridical method with descriptive data analysis. Findings indicate that according to Article 42 of Law Number 1 of 1974 concerning Marriage, a legitimate child is one born within or as a result of a lawful marriage. Through a case study of judge's decision Number 471/Pdt.P/2019/PN.DPS, the judge approved the establishment of the child because the applicants fulfilled the requirements set forth to obtain authentic evidence of their marriage. The establishment of children in mixed marriages is clearly regulated by Law Number 1 of 1974, amended by Law Number 16 of 2019 concerning Marriage. However, law enforcement regarding the establishment of children in the context of mixed marriages requires compliance with the stipulated conditions in the law to ensure the validity of the child's status.